Tools to benchmark the quality performance of a building in construction project / Khairul Ammar Muhammad Ali and Amalina Amirah Abu Bakar - Muhammad Ali, Khairul Ammar; Abu Bakar, Amalina Amirah (Unit Penerbitan PKAPP, 2024)
The Quality Assessment System in Construction Project is an impartial and objective method for measuring and evaluating the workmanship quality of construction works using applicable recognised criteria. It allows for the comparison of workmanship quality of construction projects, both relative and quantitative. Quality is very important since it ensures the customer's or purchaser's happiness. The satisfaction includes the project's performance, appearance, and dependability at the reasonable price range. The defects happened because of insufficient or poor-quality management from the beginning to the completion phase of the project.